(In)Civility: The relevance of interpersonal relationships - Gonçalves, Elsa (2017)
In order to know nurses’ reality, we conducted interviews with 19 participants from a Hospital in Lisbon, all starting with the same trigger question, analyzing the full text with the software Alceste. The results point to four distinct classes, representing the greatest influences felt by nurses’ in their daily work context.